2007
DOI: 10.1016/j.bbrc.2006.12.187
|View full text |Cite
|
Sign up to set email alerts
|

Glucose- and time-dependence of islet amyloid formation in vitro

Abstract: Islet amyloid contributes to the loss of β-cell mass in type 2 diabetes. To examine the roles of glucose and time on amyloid formation, we developed a rapid in vitro model using isolated islets from human islet amyloid polypeptide (hIAPP) transgenic mice. Islets from hIAPP transgenic and non-transgenic mice were cultured for up to 7 days with either 5.5, 11.1, 16.7 or 33.3 mmol/l glucose. At various time-points throughout the culture period, islets were harvested for determination of amyloid and β-cell areas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
50
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 26 publications
8
50
0
Order By: Relevance
“…Islets from hIAPP-expressing mice with or without caspase-3 expression had comparable levels of amyloid formation both in vitro and in vivo, confirming that the absence of caspase-3 per se does not have any detectable effect on amyloid formation in hIAPP-expressing mouse islets. As expected [16,49], hIAPP aggregates were not detectable in freshly isolated hIAPP-expressing mouse islets but were present in cultured islets. Interestingly, hIAPP-expressing islets lacking caspase-3 had markedly lower apoptotic beta cells, higher insulin content and glucose response compared with islets expressing hIAPP and caspase-3, suggesting that deletion of caspase-3 protects islet beta cells from endogenously produced hIAPP aggregates and improves their survival and function.…”
Section: Discussionsupporting
confidence: 76%
“…Islets from hIAPP-expressing mice with or without caspase-3 expression had comparable levels of amyloid formation both in vitro and in vivo, confirming that the absence of caspase-3 per se does not have any detectable effect on amyloid formation in hIAPP-expressing mouse islets. As expected [16,49], hIAPP aggregates were not detectable in freshly isolated hIAPP-expressing mouse islets but were present in cultured islets. Interestingly, hIAPP-expressing islets lacking caspase-3 had markedly lower apoptotic beta cells, higher insulin content and glucose response compared with islets expressing hIAPP and caspase-3, suggesting that deletion of caspase-3 protects islet beta cells from endogenously produced hIAPP aggregates and improves their survival and function.…”
Section: Discussionsupporting
confidence: 76%
“…Thioflavine S staining revealed the presence of clearly detectable amyloid deposits after 10-day culture of untreated human islets (Fig. 3A, top right), similar to those observed in type 2 diabetic human pancreas, suggesting that amyloid formation occurs very rapidly in cultured human islets, as in transgenic human IAPP-expressing mouse islets (23,(32)(33)(34)(35). Islets transduced with AdhProIAPP-siRNA to inhibit proIAPP expression had a marked reduction in visible amyloid (Fig.…”
supporting
confidence: 61%
“…In the present study, we tested the hypothesis that suppression of human IAPP expression would inhibit amyloid formation and enhance survival and/or function of human islets. We and others have found that islet amyloid forms rapidly in islets from transgenic mice with ␤-cell expression of human IAPP, and its formation is potentiated by elevated glucose concentrations (23,(32)(33)(34)(35). We used cultured human islets as an ex vivo model of amyloid formation to investigate whether short interfering RNA (siRNA)-mediated suppression of endogenously expressed human proIAPP will enhance ␤-cell survival in human islets.…”
mentioning
confidence: 99%
“…Although we cannot rule out effects on the islet secondary to macrophage depletion in other tissues, wild-type mice displayed no change in glucose tolerance in response to clodronate liposomes, suggesting a unique role for macrophages in the setting of hIAPP aggregation. We observed improved glucose-stimulated insulin secretion in isolated islets from clodronate liposome-treated hIAPP Tg/o mice and in clodronate liposome-treated hIAPP Tg/o islets cultured in high glucose, conditions demonstrated by others to promote amyloid formation (54). Thus, improved b-cell function caused by macrophage depletion in vivo may be largely independent of peripheral effects.…”
Section: Discussionsupporting
confidence: 49%